Efeito de novos compostos derivados da Protoporfirina IX associados à terapia fotodinâmica em Leishmania - Chaves, Cíntia de Campos (2025)
Leishmaniasis is a neglected tropical disease and a major public health problem. In the Americas, American Tegumentary Leishmaniasis (ATL), caused by New World species, stands out. Current treatment involves pentavalent antimonials and amphotericin B, both of which carry high risks of toxicity and resistance.Photodynamic therapy (PDT) presents a promising alternative, especially for cutaneous leishmaniasis, due to its potential for localized action and low toxicity. PDT uses a photosensitizer which, when activated by light, generates reactive oxygen species, causing cellular damage. This study evaluated the anti-Leishmania potential of two new Protoporphyrin IX (PpIX) derivatives, PpIX-Morpholine (PS1) and PpIX-Methyl-Piperazine (PS2), in combination with PDT against L. (L.) amazonensis, L. (V.) braziliensis, and L. (V.) guyanensis, highlighting their cytotoxic potential against promastigote forms and their effects on parasite-host interaction. Cytotoxicity was analysed via MTT assay on promastigote forms of the different parasite species and on murine macrophages (RAW 264.7). The effects of PS1 and PS2 were also evaluated in an in vitro infectivity assay using non-toxic doses for 90% of RAW 264.7 macrophages. Light-exposed PS1 and PS2 exhibited potent cytotoxic activity against all Leishmania species tested. The IC50 values ranged from 1.10–3.46 μM for PS1 and 1.78–4.71 μM for PS2. Light-exposed PS1 and PS2 significantly inhibited Leishmania amazonensis infectivity compared to the lightexposed untreated control, with inhibition percentages ranging from 73–96% for PS1 and 67–79% for PS2. The reductions in infectivity primarily resulted from decreases in the percentage of infected macrophages. The results presented here suggest remarkable in vitro leishmanicidal activity by these new photosensitizers.